Parenting styles, psychological need and game genre in internet gaming disorder - V., Shimil P.; Kanwar, Palak (International Journal of Public Health Science (IJPHS), 2025)
Internet gaming disorder (IGD) is a growing concern among adolescents. This study examines the impact of different parenting styles on IGD, focusing on the mediating role of psychological need satisfaction. Using a cross-sectional correlational design with mediation analysis, this research investigates indirect effects to understand how parenting styles influence IGD. The study involved 300 participants and analyzed three main parenting styles: authoritative (firm but supportive), authoritarian (strict and controlling), and permissive (lenient). Findings indicate that authoritative parenting reduces IGD by supporting the fulfillment of basic psychological needs, such as autonomy, competence, and connection, as outlined in self-determination theory (SDT). Conversely, authoritarian parenting is associated with higher IGD, as it restricts these psychological needs in real life, leading adolescents to seek fulfillment through excessive gaming, particularly in genres like battle royale. permissive parenting did not show a significant effect on IGD. Additionally, the study revealed that boys are more likely than girls to exhibit higher IGD and find greater psychological need satisfaction in gaming. These results highlight the importance of parenting styles and psychological needs in understanding IGD among adolescents.